2015
DOI: 10.1007/s10067-015-2872-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of B lymphocyte stimulator inhibitor belimumab may be associated with a decrease in the serum concentration of epidermal growth factor in patients with primary Sjögren’s syndrome

Abstract: B cell activating factor (BAFF), also called the B lymphocyte stimulator, has been known to show increased expression in primary Sjögren's syndrome (pSS) which could explain increased B cell activation characteristic of this disease. Belimumab, a fully human IgG1λ recombinant monoclonal antibody directed against B lymphocyte stimulator (Blys), has been reported to be efficacious in systemic lupus erythematosus (SLE) through its B cell-mediated action. Randomized controlled trials of belimumab in a selected tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Thus, specifically depleting the active B cells or plasmocyte may represent a promising approach to slowing diseases progress. Current monoclonal antibodies such as Rituxan and Belimumab have achieved some positive effects in clinics 55 , 56 , whereas the drug response remains unsatisfied because of heterogeneity of autoantigens in patients. Subsequently, more broad-spectrum strategies that can neutralize these autoantibodies should be developed.…”
Section: Bioinspired Membrane Coating Nanoplatform In Autoimmune Dise...mentioning
confidence: 99%
“…Thus, specifically depleting the active B cells or plasmocyte may represent a promising approach to slowing diseases progress. Current monoclonal antibodies such as Rituxan and Belimumab have achieved some positive effects in clinics 55 , 56 , whereas the drug response remains unsatisfied because of heterogeneity of autoantigens in patients. Subsequently, more broad-spectrum strategies that can neutralize these autoantibodies should be developed.…”
Section: Bioinspired Membrane Coating Nanoplatform In Autoimmune Dise...mentioning
confidence: 99%
“…This study suggests that low blood and salivary NK cell numbers may serve as predictors for a better belimumab response in pSS [ 45 ]. A retrospective off-label chart review study reported that treatment with belimumab led to significantly lower epidermal growth factor (EGF) concentrations [ 46 ], although the role of EGF in the pathogenesis or development of pSS remains elusive. A large RCT is needed to solidify the abovementioned findings.…”
Section: B Cell-targeted Biologic Therapiesmentioning
confidence: 99%